Pendekatan Multikultural Dalam Pendidikan Agama Islam: Studi Pustaka Atas Implikasinya Pada Kurikulum - Khairi, Ahyal; Azka, Zumratul; Hidayah, Nurul (Studi Multidisipliner: Jurnal Kajian Keislaman, 2025)
This study examines multicultural approaches in Islamic Religious Education with an emphasis on developing tolerance, inclusion, and understanding of students' religious practices and cultural backgrounds. In practice, the application of a multicultural approach in Islamic Religious Education still faces various challenges in the field. Although the curriculum and education policies point to the importance of building attitudes of tolerance, inclusion, and understanding of religious and cultural diversity. This research uses the library research method. The data sources used include scientific books, academic journals, articles, education policy documents, and the results of previous research that discuss the concepts of multiculturalism, religious education, and the development of the values of tolerance, inclusion, and understanding of cultural and religious diversity. The data analysis technique used is content analysis, which aims to identify, understand, and critically examine various concepts, approaches, and implementation of multicultural values in the context of Islamic Religious Education. The results of the study show that the multicultural approach in Islamic Religious Education has great potential in forming attitudes of tolerance, inclusion, and understanding of diversity among students. In his contribution, it was found that this approach emphasizes not only the cognitive aspects of understanding religious teachings, but also the affective and social aspects that encourage appreciation for students' cultural differences, beliefs, and social backgrounds.